(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Veronica E, Ardianor, Dohong S, Asi N, Afentina, Hanasia. 2025. Moonlight-driven zooplankton migration shapes phytoplankton distribution in a tropical peatland pond. Biodiversitas 26: 4746-4760. The interaction between phytoplankton and zooplankton plays a vital role in regulating aquatic ecosystem dynamics. This study explored the vertical distribution of phytoplankton in relation to zooplankton abundance under varying lunar light conditions and assessed the influence of selected physicochemical parameters. The research was conducted in Beje Pond, Peat Techno Park (PTP), Universitas Palangka Raya, Central Kalimantan, Indonesia, with sampling performed at seven depth intervals (0-180 cm) every three days over a one-month period. A total of 20 phytoplankton species were identified, with seven dominant taxa consistently observed: Chlamydomonas nivalis, Chlorogonium elongatum, Asterococcus superbus, Staurastrum tetracerum, Zygnema sp., Closterium praelongum, and Skeletonema costatum. Phytoplankton abundance ranged from 810 to 2,232 cells/L, peaking during half-moon conditions. Zooplankton abundance reached a maximum of 765 ind/L during the ninth sampling under dim moonlight, with apparent temporal offset from phytoplankton peaks. This pattern suggests the possibility of zooplankton diel vertical migration modulated by lunar illumination. Principal Component Analysis (PCA) showed that Dissolved Oxygen (DO), temperature, and pH together accounted for 84.6% of the environmental variance. Spearman correlation analysis indicated significant positive correlations (p < 0.05) between DO and phytoplankton abundance (r = 0.59), and between phytoplankton and zooplankton (r = 0.53). No significant correlations were observed between pH and phytoplankton or between DO and zooplankton. While patterns suggest possible vertical variation linked to diel cycles and lunar phase, these findings remain correlative. Further integrative studies are recommended to investigate the ecological mechanisms driving these distributions in tropical peatland waters.